Impact of daily artificial gravity on autonomic cardiovascular control following 60-day head-down tilt bed rest - Hoenemann, J.-N.; Moestl, S.; Diedrich, A.; Mulder, E.; Frett, T.; Petrat, G.; Pustowalow, W.; Arz, M.; Schmitz, M.-T.; Heusser, K.; Lee, S. M. C.; Jordan, J.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Impaired cardiovascular autonomic control following space flight or immobilization may limit the ability to cope with additional hemodynamic stimuli. Head-down tilt bedrest is an established terrestrial analog for space flight and offers the opportunity to test potential countermeasures for autonomic cardiovascular deconditioning. Previous studies revealed a possible benefit of daily artificial gravity on cardiovascular autonomic control following head-down tilt bedrest, but there is a need for efficiency in a long-term study before an artificial gravity facility would be brought to space. We hypothesized that artificial gravity through short-arm centrifugation attenuates functional adaptions of autonomic function during head-down tilt bed rest. 24 healthy persons (8 women, 33.4 ± 9.3 years, 24.3 ± 2.1 kg/m2) participated in the 60-day head-down tilt bed rest (AGBRESA) study. They were assigned to three groups, 30 min/day continuous, or 6(5 min intermittent short-arm centrifugation, or a control group. We assessed autonomic cardiovascular control in the supine position and in 5 minutes 80° head-up tilt position before and immediately after bed rest. We computed heart rate variability (HRV) in the time (rmssd) and frequency domain, blood pressure variability, and baroreflex sensitivity (BRS). RR interval corrected rmssd was reduced supine (p = 0.0358) and during HUT (p = 0.0161). Heart rate variability in the high-frequency band (hf-RRI; p = 0.0004) and BRS (p < 0.0001) decreased, whereas blood pressure variability in the low-frequency band (lf-SBP, p = 0.0008) increased following bedrest in all groups. We did not detect significant interactions between bedrest and interventions. We conclude that up to daily 30 min of artificial gravity on a short-arm centrifuge with 1Gz at the center of mass do not suffice to prevent changes in autonomic cardiovascular control following 60-day of 6° head-down tilt bed rest. Clinical Trial Registration: https://drks.de/search/en/trial/DRKS00015677, identifier, DRKS00015677